2012
DOI: 10.1093/ckj/sfs055
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of the primary vascular access and its translation into prevalent access use rates in chronic haemodialysis patients

Abstract: BackgroundThe American Fistula First Breakthrough Initiative currently aims for a 66% arterio-venous fistula (AVF) rate, while in the UK, best practice tariffs target AVF and arterio-venous graft (AVG) rates of 85%. The present study aims to assess whether these goals can be achieved.MethodsWe conducted a retrospective cohort study on patients who initiated haemodialysis from 1995 to 2006. Outcomes were the final failure-free survival of the first permanent access and the type of second access created. Prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…It has been suggested that worse AVF maturation outcomes in females may be due to smaller baseline blood vessel diameters relative to males (9). Yet a number of subsequent studies have reported that females have inferior rates of AVF maturation than males, despite similar preoperative vascular diameters, consistent with this study’s findings (7,12 14). Of note, on multivariable analysis, female sex was no longer an independent predictor of AVF nonmaturation, whereas Black race persisted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been suggested that worse AVF maturation outcomes in females may be due to smaller baseline blood vessel diameters relative to males (9). Yet a number of subsequent studies have reported that females have inferior rates of AVF maturation than males, despite similar preoperative vascular diameters, consistent with this study’s findings (7,12 14). Of note, on multivariable analysis, female sex was no longer an independent predictor of AVF nonmaturation, whereas Black race persisted.…”
Section: Discussionsupporting
confidence: 90%
“…A study using the Hemodialysis Fistula Maturation (HFM) cohort reported that early AVF thrombosis was three times higher in females vs males, and twice as high in Black vs white patients, although this racial difference was not statistically significant (11). Sex and racial disparities in AVF maturation outcomes are not adequately explained by differences in clinical characteristics or pre-operative blood vessel diameters, suggesting that additional unidentified factors contribute to AVF non-maturation, especially in the populations at risk for poor AVF maturation outcomes (7,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that high AVG use is an area of low-value care that can be addressed at the surgeon level. Most previously published literature reporting trends of hemodialysis access focus on the type of access used at the time of incident hemodialysis 3,12 or rates of prevalent dialysis access type. 7, 11,16 Lynch et al 7 reported that the percentage of US facilities achieving the 66% AVF goal increased from 6.4% in 2007 to 19.0% in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The type of hemodialysis access chosen for a patient has a direct effect on complication rates and health care costs. Typically, complications and mortality are significantly lower with arteriovenous fistula (AVF) compared with arteriovenous graft (AVG) or central venous catheter use . In addition, the cost associated with an AVF ($60 000 per person per year) is markedly lower than the cost of an AVG ($72 729 per person per year) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation